A organização de unidades do conhecimento em hiperdocumentos: o modelo conceitual como um espaço comunicacional para realização da autoria - Campos, Maria Luiza de Almeida (2001)
Lack of appropiate methodologies for conceptual models to represent knowledge units in the production of hyperdocuments is verified in the literature. No appropriate criteria in this activity lead to deterioration of communication between the author of subject content and the system analyst. As a consequence, the development and deployment of hyperdocuments is damaged. Definition of criteria to aid in the creation of methodologies for developing conceptual models should be done through as interdisciplinary approach envolving subject fields such as Information Science, Computer Science and Terminology. Those criteria are equally valid to modeling data base systems and to systems aiming at the organization of knowledge units such as hyperdocuments. In Information Science the study focused on the Theory of Classification; in Computer Science, on Ojject-Oriented methodologies and Ontologies. The latter ones, as well as Terminology, have in common classifrcatory bases aiming at concepts systems both to structure a subject field and to define concepts. This research lead to a set of requirements based on a comparative analysis of those methods and theories that may help in the development of methodologies for conceptual models to be used when designing hyperdocuments